QUALITY OF LIFE AT WORK IN A READY CARE UNIT (UPA) IN BRAZIL DURING THE COVID-19 PANDEMIC - de Oliveira Lima, Lucas Alves; Domingues, Paulo Lourenço; de Oliveira Lima, Matheus Alves; Barros Duarte, Gabriela Halfeld (International Journal of Research -GRANTHAALAYAH, 2020)
The advent of the COVID-19 pandemic has brought about drastic changes in people’s lives. In this scenario, health professionals became susceptible to acquire occupational diseases and began to have their work routine affected by the high demand for care to the infected. Therefore, this study aimed to understand the main factors that are harming the quality of life at work of professionals at a Ready Care Unit (Unidade de Pronto Atendimento - UPA) in the municipality of Três Rios/RJ during the pandemic scenario. This is an exploratory qualitative approach survey, which was conducted through a semi-structured interview with a non-probabilistic sample of fifteen employees. For the data analysis, we resorted to discourse analysis, where it was possible to verify that the main factors that are hindering the employees are: the lack of personal protection equipment (PPE), inadequate infrastructure and the absence of training. In addition, it was also found that the employees were not infected by the new coronavirus, but most have acquired some kind of psychological problem such as insomnia, mental fatigue, excessive stress or sadness. Such diseases mainly affect women with double work hours, thus showing a greater vulnerability among female individuals.